Elucidating mechanisms of thermodynamic detoxification and conformational engineering of Lemna minor RuBisCO: in situ pickering armor cross-linking in cryoresistant hybrid cheese models - Pang, Yongfeng; Helikh, Anna; Filon, Andrii (Eastern-European Journal of Enterprise Technologies, 2026)
This study focuses on the design of cryoresistant buffalo cheese models, in which the lipid phase is volumetrically replaced by a Pickering emulsion gel based on a RuBisCO isolate derived from Lemna minor biomass. The core problem addressed is the limited upcycling potential of this phytoremediant into sustainable alternative proteins, caused by heavy metal hyperaccumulation during biomass harvesting in contaminated military and industrial biotopes. Results demonstrate that a thermodynamic detoxification protocol (acid shock at pH 3.0 and dialysis) reduced the initial concentrations of Pb (6.9 mg/kg) and Cd (0.6 mg/kg) to < 0.10 mg/kg (efficiencies of ≥ 98.5% and ≥ 83.3%, respectively) and Cu levels by ≥ 84.6%, ensuring the production of a decontaminated isolate. The resulting isolate underwent conformational engineering (a pH-shift from 11.0 to 7.0) to form nanoparticles that stabilized the initial Pickering emulsion. Following ionotropic gelation, the emulsion was utilized for the volumetric replacement of animal fat by up to 75%. Gel integration substantially enhanced the water-holding capacity of the system (up to 87%) and minimized cryo-syneresis (from 14% to 1.5%). During the Schreiber test (85°C), the hybrid model exhibited a transition from a viscoelastic melt to a thermostable gel with suppressed lipid exudation. These macroscopic effects are attributed to enhanced polymer hydration, Donnan osmotic swelling, and the spatial restriction of capillary water mobility. The observed structural transition and thermostability are likely driven by synergistic in situ interfacial cross-linking of the Pickering armor, disulfide bond formation, and thermally induced macromolecular consolidation indicative of late-stage Maillard reactions. The stability of this rheological test system confirms the efficacy of upcycling phytoremediants for non-food applications and the feasibility of extrapolating the protocol to standard food raw materials